Heart failure in children: co-morbidities and hospital outcome (Bangladesh Medical Journal, 2019)
Heart failure in children is a serious condition, causes substantial morbidity and mortality. Sufficient data regarding various aspects of heart failure in children is not available in our country. This cross sectional study was conducted on 101 patients admitted with the diagnosis of heart failure at ICMH, and NICVD from July 2014 to March 2015 with the aim to identify the co-morbidities and hospital outcome of heart failure in infants and children. In this study most of the patients (53.46%) were infants. Congenital structural heart lesions were found in 67(76.2%) cases. VSD was most common found in 42.5% cases, followed by ASD (31.6%) and PDA (24.7%). Cardiomyopathy (DCM) was diagnosed in 11 (10.9%) cases and 10 patients (9.9%) had valvular defect due to rheumatic recurrence. Anaemia was most common (78.2%) co-morbidity in all age group. Pneumonia was more common (74%) in infants. Total 14 patients (13.9%) died in hospital though getting adequate medical support. This study recommends that diagnosis and treatment of co-morbidities along with appropriate management of acute heart failure is crucial to reduce the mortality and morbidity.Bangladesh Med J. 2018 Jan; 47 (1): 6-10